The Castle in Zeist and its residents from 1745 to 1924 (Bulletin KNOB, 2002)
At the time of its completion in 1686 Zeist castle was the most prestigious project ever realised on the range of hills near Utrecht ('Utrechtse Heuvelrug'). By this project commissioner Willem Adriaan van Nassau-Odijk rivalled with his second cousin, king-stadtholder Willem III, who had made a start with the renovation of Het Loo in the same period. After having been owned by the Van Nassau-Odijk family for sixty years, 'Huys van Zeyst' with the large park and the surrounding grounds was sold to the Zeist Community of the Moravian Brethren in 1745.So far, the history of Zeist castle between 1745 and 1924, the year when private occupation definitely came to an end, has not been sufficiently elucidated. Various publications appeared on its construction in the 17th century and restoration in the sixties of the 20th century. The intervening period appears to have been much more varied than assumed so far. It is more than the history of an extraordinary building, more than the development of a park, more than a family history.With its sale in 1745 the use of the house changed. The successive owners did not live there themselves, but rented out the building in parts. Initially all this did not have many consequences for the layout of the garden. That did not happen until after 1830, when the house and part of the park came into possession of the Huydecoper family. During the Huydecopers' ownership the formal park was given a landscape layout by J.D. Zocher Jnr. The house was also radically dealt with, refurnished and made suitable for occupation by one family.Sales notes, inventories of the furnishings and photographs provide information on the use of and changes in the house. Prints and drawings evoke an image of the park in the 18th and 19th centuries and give an impression of the layout and type of planting.Although the Huydecoper family did not live in Zeist castle all year through, it appears from the inventory of the furnishings that the lord of Zeist lived in great style and used all the rooms in the house intensively. This style of living was continued by their successors, the Labouchere family and did not terminate until 1924, when the castle was purchased by the municipality of Zeist.The presence of the castle and its layout were decisive for the development of the surroundings. The structure of the 17th-century park is still visible under the 18th- and 19th-century alterations and the 20th-century buildings.The fact that in 1830 J.E. Huydecoper had not acquired the entire former Nassau property - it had already been sold in parts previously, in 1818 - made a new development possible. The various buyers who had been able to secure a part, could realise their own country estate there, a house with annexes in a park layout. This was to be the start of a boom in the Utrecht range of hills, later known as 'De Stichtse Lustwarande' (pleasure grounds), the layout of a belt of country estates from De Bilt to far beyond Doorn, with a high concentration in Zeist.